Reflective learning for behavioral guidance in pediatric dentistry - Richa Khanna; Rajeev Kumar Singh; Rameshwari Singhal (Wolters Kluwer Medknow Publications, 2020)
Introduction: Basic behavioral guidance (BBG) skills help in delivery of quality health care in pediatric dentistry. The complex nature of these skills, warrants analyzing actions performed. An appropriate scientific way to do this is by "reflection." Hence, the present study was designed to introduce "reflection of action" as means for learning BBG skills by undergraduates in pediatric dentistry. Materials and Methods: Participants (dental undergraduate) performed oral prophylaxis (two visits) in pediatric patients (age 3-7 years) with application of BBG skills, under video recording. They were instructed regarding "reflection on action." The learners then reviewed own videos and wrote reflections. Reflections were assessed on Boud's 4R framework and feedback was given by the faculty. Reflective writing was repeated for a second visit. Knowledge of the learners in using reflections for learning was assessed by retrospective pretest posttest questionnaire. Video recordings were scored for BBG skills. Acceptability of the intervention was addressed by satisfaction questionnaire. Results: There was a significant improvement in the knowledge of participants in using reflections for learning these skills. All participants were able to "revisit" (R1 level under Boud's 4R framework) patient encounter in their written reflections. Sixteen participants exhibited shift toward higher levels in the next visit. Video scores of learners also improved significantly over both visits. Students were satisfied with the content, delivery, and relevance of the new educational intervention. Conclusion: The strong need of improving BBG skills in pediatric dentistry was met by "reflection on action." There was improvement in the knowledge of students in using reflections for learning and application of behavior guidance skills and was well accepted.